2000
DOI: 10.1021/jp002856w
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Interaction of [Ru(phen)2(dppz)]2+ with Single-Stranded DNAWhat Degree of Protection Is Required for Operation of the “Light-Switch Effect”?

Abstract: Time-resolved and steady-state luminescence and transient resonance Raman measurements have been carried out on the complex [Ru(phen) 2 dppz] 2+ (1) in the presence of single-stranded (ss) DNA that is either covalently attached to or mixed in 1:1 ratio with the complex. The well-known enhancement of luminescence (the "lightswitch" effect) exhibited by (1) when intercalated to double-stranded DNA is also observed in the presence of the single-stranded material, under conditions of covalent attachment or simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
81
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 12 publications
11
81
0
Order By: Relevance
“…This conclusion is in contrast with the case of [Ru(phen) 2 complex was affected by the length and nature of the base. 15,16 Therefore, it was concluded that for the [Ru(phen) 2 -DPPZ] 2+ complex both the base and phosphate group are involved in the luminescent complex.…”
Section: +mentioning
confidence: 99%
See 4 more Smart Citations
“…This conclusion is in contrast with the case of [Ru(phen) 2 complex was affected by the length and nature of the base. 15,16 Therefore, it was concluded that for the [Ru(phen) 2 -DPPZ] 2+ complex both the base and phosphate group are involved in the luminescent complex.…”
Section: +mentioning
confidence: 99%
“…11 However, the mechanism for the light switch effect of the [Ru(phen) 2 DPPZ] 2+ complex upon its association with single stranded DNAs is not clear yet, because the single stranded DNA cannot provide any intercalation pocket, i.e., non-polar environment for the incoming Ru(II) complex. 15,16 In the case of the [Ru(phen) 2 BDPPZ] 2+ complex, the luminescence quantum yield decreases proportionally with respect to the solution's polarity except in the cases of DMF and MeCN. Although the reason for these two exceptions is unclear, the "light switch off" effect of the [Ru(phen) 2 -BDPPZ] 2+ complex may be attributed to the increase in the environmental polarity upon its association with the negatively charged phosphate groups of the single stranded 2+ complex in the presence of single stranded DNAs are also pronounced.…”
Section: +mentioning
confidence: 99%
See 3 more Smart Citations